Transformative Management of Religious Programs in Islamic Elementary Education - Fahmi, Robith (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
The transformation of Islamic elementary education requires educational institutions to strengthen not only academic achievement but also students’ religious character through sustainable and value based educational management. This study aimed to analyze the transformative management of religious programs in Islamic elementary education, particularly regarding strategic planning, participatory implementation, continuous supervision, and institutional religious culture transformation in strengthening students’ Islamic character at MI Miftahul Mlokorejo Jember. This research employed a qualitative approach using a case study design to obtain an in depth understanding of managerial practices and institutional dynamics underlying the implementation of religious programs within the madrasah environment. Data were collected through in depth interviews, participant observation, and documentation studies involving the madrasah principal, vice principal, teachers, religious program coordinators, students, and parents. The collected data were analyzed using interactive thematic analysis through data condensation, data display, and conclusion drawing, while data validity was ensured through triangulation, member checking, and prolonged engagement. The findings revealed that the transformative management of religious programs was implemented systematically through collaborative planning, participatory implementation, continuous supervision, and sustainable institutional culture transformation. Religious programs such as congregational prayer, Qur’anic recitation, tahfidz activities, Islamic speech training, and charity programs were integrated into the daily culture of the madrasah and contributed significantly to strengthening students’ religious discipline, spiritual awareness, empathy, social responsibility, and Islamic identity. The study further found that teachers’ exemplary behavior, parental collaboration, and institutional religious culture played crucial roles in supporting the sustainability and effectiveness of religious programs. The novelty of this study lies in its focus on transformative management of religious programs at the Madrasah Ibtidaiyah level through an integrative framework combining leadership transformation, institutional culture development, participatory governance, and sustainable religious habituation. This study also contributes theoretically to the discourse of Islamic educational management by offering a comprehensive perspective on transformative religious program management in Islamic elementary education. Practically, the findings provide strategic insights for madrasah leaders, teachers, and policymakers in developing sustainable religious programs capable of strengthening Islamic character formation and institutional transformation within contemporary Islamic educational contexts.